Add or substract. Simplify if possible. \( \frac{16+x}{x^3}+\frac{7-4x}{x^3}\);
\( \frac{5}{t-1} +\frac{3}{t} \)

\( \frac{16+x}{x^3}+\frac{7-4x}{x^3}=\frac{16+x+7-4x}{x^3}=\frac{23-3x}{x^3}\\\\=========\\\\\frac{5}{t-1}+\frac{3}{t}=\frac{5t}{t(t-1)}+\frac{3(t-1)}{t(t-1)}=\frac{5t+3t-3}{t^2-t}=\frac{8t-3}{t^2-t} \)

\( \frac{16+x}{x^{3} } + \frac{7-4x}{ x^{3} } \\ 16+x+7-4x = 23-3x \\ \frac{23 -3x}{ x^{3} } \)
~~~~~~
\( \frac{5}{t-1} +\frac{3}{t} \\ \\ \frac{5t+(t-1)(3)}{(t-1)(t)} \\ \\ \frac{5t+3t-3}{ t^{2}-t } \\ \\ \frac{8t-3}{ t^{2}-t } \)


RELATED: